Identification of a VapA virulence factor functional homolog in Rhodococcus equi isolates housing the pVAPB plasmid. - Jennifer M Willingham-Lane; Garry B Coulson; Mary K Hondalus (PLoS ONE, 2018)
Rhodococcus equi is a facultative intracellular bacterium of macrophages and is an important pathogen of animals and immunocompromised people wherein disease results in abcessation of the lungs and other sites. Prior work has shown that the presence of the major virulence determinant, VapA, encoded on the pVAPA-type plasmid, disrupts normal phagosome development and is essential for bacterial replication within macrophages. pVAPA- type plasmids are typical of R. equi strains derived from foals while strains from pigs carry plasmids of the pVAPB-type, lacking vapA, and those from humans harbor various types of plasmids including pVAPA and pVAPB. Through the creation and analysis of a series of gene deletion mutants, we found that vapK1 or vapK2 is required for optimal intracellular replication of an R. equi isolate carrying a pVAPB plasmid type. Complementation analysis of a ΔvapA R. equi strain with vapK1 or vapK2 showed the VapK proteins of the pVAPB-type plasmid could restore replication capacity to the macrophage growth-attenuated ΔvapA strain. Additionally, in contrast to the intracellular growth capabilities displayed by an equine R. equi transconjugant strain carrying a pVAPB-type plasmid, a transconjugant strain carrying a pVAPB-type plasmid deleted of vapK1 and vapK2 proved incapable of replication in equine macrophages. Cumulatively, these data indicate that VapK1 and K2 are functionally equivalent to VapA.